"Come Together": Dialogue and (Dis)Connection in the Beatles' Lyrics. Issue 2 (4th May 2017) - Lieberfeld, Daniel
Abstract: The article analyzes the Beatles' 183 original recorded lyrics as a body of work, highlighting the lyrics' thematic diversification and increasing narrative complexity as of 1965–66. Dialogical elements characterizing many Beatles lyrics extended to audiences the sense of collective intimacy that formed the core of the band's identity and appeal. Group vocal arrangements on Sergeant Pepper's Lonely Hearts Club Band permitted "heteroglossic dialog" through which the writers expressed and sought to reconcile the cultural and social tensions they perceived in their own lives and in the wider world. Lyrical innovations enabled the authors to respond to social and cultural currents—particularly how electronic media, drugs, and spiritual practices could bridge social, political, and interpersonal divisions and distances, yet also foster isolation and self-absorption. Lyrics on Pepper articulate this dialectic of connection and atomization.